Patient-reported outcomes in large vessel vasculitis: insights from a retrospective analysis of disease activity and associated factors - A. Kernder; M. Rohde; H. Acar; C. Düsing; R. Fischer-Betz; I. Haase; J. Mucke; O. Sander; J. G. Richter; T. Filla; M. Schneider; G. Chehab (SpringerOpen, 2024)
Abstract Background Patient-reported outcomes (PROs) play a crucial role in assessing rheumatic diseases, offering insights into disease evaluation and treatment efficacy. This study focuses on PRO assessment in large vessel vasculitides, including Takayasu Arteritis and Giant Cell Arteritis (GCA). Methods We retrospectively analyzed routine data from patients treated at our rheumatology clinic over a 10-year span. Patient and physician-rated global disease activity scale (G-DAS) scores, measured on a numeric rating scale (0-10 points), were collected at each visit. Clinical variables like age, sex, body mass index (BMI), disease duration, lab values, pain perception, and questionnaire responses were recorded. Linear regression and generalized additive linear regression (GAM analysis) examined associations between PROs and these factors. Results The study included 138 patients, primarily diagnosed with GCA (94.4%). Mean follow-up was 2.5 years (0-7.7). Patient and physician G-DAS exhibited a moderate correlation (Pearson R 0.19, CI 0.14-0.24, p < 0.001). Higher patient G-DAS correlated with younger age (CI -3.4 - -1.5, p < 0.001), increased pain (CI 3.5-4, p < 0.001), functional limitations (HAQ, CI 0.5-0.6, p < 0.001), reduced physical (CI 2.3-2.7, p ≤ 0.001) and psychological well-being (CI 2.1-2.5, p < 0.001), and higher BMI (CI 1.3-2.4, p < 0.001). Physician G-DAS correlated with Birmingham Vasculitis Activity Score (V3.0; R 0.42, p 0.046) and were significantly linked to serum CRP elevations (β = 0.04, CI 0.0-0.08, p 0.028). Conclusions These findings underscore the need to integrate PRO measures into vasculitis disease management strategies, enhancing the understanding of disease activity from the patient's perspective.